KEBIJAKAN PENDIDIKAN PROVINSI (SLTA DAN SMK) DAN ANALISIS SWOT DI KALIMANTAN TIMUR - Iwan Heriawan (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2018)
Public policy is one of the implementations of formal high school and SMKA education management by the provincial government while the elementary, junior and senior high school levels are managed by the district and city governments and refer to Law Number 23 of 2014 concerning Regional Government and revised by the Republic of Indonesia Law Number 9 of 2015 states that dividing government affairs between the central, provincial and district or city governments, especially in the field of education. Relating to the policy of implementing education in a decentralized or fully autonomous manner, it is managed by the provincial government, one of which is the management of high school and vocational schools. The education autonomy policy is meant to include management of education, teaching staff, education facilities and infrastructure, and education budget including the welfare of education and placement of educators. The provincial education policy is a strategic sign for measuring the annual performance of the East Kalimantan Provincial Government as one of the efforts to improve the performance of the East Kalimantan Provincial Government in the fields of senior high school and vocational high school education. Provincial education policies can be realized objectively transparently, and evidenced by the number or quantity of high school and vocational education institutions, especially teachers either civil servant or honorary status. Provincial education policies at the high school and vocational level can implement SWOT strategic planning management to measure, supervise, and evaluate strengths, weaknesses, opportunities, and challenges and formulas for strategic plans.